Why Research in Sustainable Supply Chain Management Should Have no Future. Issue 1 (January 2014) - Pagell, Mark; Shevchenko, Anton
<x xml:space="preserve">Abstract</x> In the last two decades, the topic of sustainability has moved from the fringes of supply chain management research to the mainstream and is now an area of significant research activity. In this paper, we argue that while this increase in acceptance and activity is welcome and has lead to a greater understanding of sustainability, our present knowledge is not sufficient to create truly sustainable supply chains. We build on this insight to identify five main issues that future research needs to address. We argue that when it comes to the theory of sustainable supply chain management, previous research has focused on the synergistic and familiar while overlooking trade‐offs and radical innovation. These theoretical issues are compounded by measures that do not truly capture a supply chain's impacts and methods that are better at looking backwards than forwards. The paper concludes by proposing a series of recommendations that address these issues to help in the development of truly sustainable supply chains.